2022
DOI: 10.1097/sap.0000000000003238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preconditioning With Transcutaneous Electrical Nerve Stimulation Monitored by Infrared Thermography on the Survival of Pedicled Perforator Flaps in a Rat Model

Abstract: Objective: Pedicled perforator partial or complete necrosis with a rate of 13.7%. This study was undertaken to test whether preconditioning with transcutaneous electrical nerve stimulation (TENS) monitored by infrared thermography protect against partial necrosis by converting the choke anastomoses to the true anastomoses via inducing heme oxygenase-1 (HO-1) in a rat pedicled perforator flap model. Methods: Seventy-two Sprague-Dawley rats were randomly assigned to the control, the TENS, the TENS + SnPP (tin pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Future studies on the pan‐plexus injury repair rat model will be necessary to better corroborate the efficacy of HO‐1 on neuromusculoskeletal protection. Assuming that HO‐1 is capable of preserving mass and ultrastructural characteristics in denervated muscle over long periods of time in humans, muscle‐targeted upregulation of HO‐1 in a noninjurious, clinically feasible manner, such as passive heat or electrical stimulation, 38,39 may be an effective adjunct treatment to improve hand function in children with pan‐plexus injury.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies on the pan‐plexus injury repair rat model will be necessary to better corroborate the efficacy of HO‐1 on neuromusculoskeletal protection. Assuming that HO‐1 is capable of preserving mass and ultrastructural characteristics in denervated muscle over long periods of time in humans, muscle‐targeted upregulation of HO‐1 in a noninjurious, clinically feasible manner, such as passive heat or electrical stimulation, 38,39 may be an effective adjunct treatment to improve hand function in children with pan‐plexus injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies such as acupuncture, photo biomodulation, electrostimulation, or thermotherapy can modify the superficial thermal response associated with the inflammatory process and pain [ 22 , 23 , 24 ]. Some studies have shown that, for example, electrostimulation with transcutaneous electrical nerve stimulation (TENS) prevents tissular necrosis [ 25 ], while high-intensity laser therapy applied to racehorses with back pain has been shown to decrease the palpation score for pain [ 26 ]. Although further studies are required, these events may show a distinct thermal response when evaluated through IRT [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%